An Examination of a Multitiered System of Language Support for Culturally and Linguistically Diverse Preschoolers: Implications for Early and Accurate Identification. Issue 1 (1st March 2016) - Weddle, Sarah A.; Spencer, Trina D.; Kajian, Mandana; Petersen, Douglas B.
Abstract: A disproportionate percentage of culturally and linguistically diverse students have difficulties with language-related skills that affect their academic success. Early and intensive language instruction may greatly improve these students' language skills, yet there is not sufficient research available to assist educators and school psychologists in distinguishing between language disabilities and language differences. Because of this, culturally and linguistically diverse children often receive special education services several years later than other children. The purpose of the study was to investigate the effect of a multitiered intervention on the narrative language skills of seven culturally diverse preschool students. We also examined the preventive impact the narrative language intervention had on special education referrals. Results of the multiple baseline design across participants revealed that a positive trend emerged in retells and personal stories from baseline to intervention for all seven participants. At follow-up, scores remained consistently above baseline. The intervention had a preventive impact for six preschoolers, and only one preschooler was referred for a psychoeducational evaluation. These findings support the use of narrative intervention to prevent erroneous referrals of culturally and linguistically diverse students.